Computing the Zagreb eccentricity indices of thorny graphs - Berberler, Zeynep Nihan (Utilitas Mathematica, 2019)
The first and second Zagreb eccentricity indices are defined respectively in terms of the vertex eccentricities as Ex ( G) =e ( k)2 and= where e(u) denotes the eccentricity of thevertex U. In this paper, Zagreb eccentricity indices of a class of composite graphs, namely, thorny graphs are investigated. Explicit formulas for Zagreb eccentricity indices of these types of graphs are presented. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.